1984
DOI: 10.1901/jeab.1984.42-239
|View full text |Cite
|
Sign up to set email alerts
|

Signal Functions in Delayed Reinforcement

Abstract: Three experiments were conducted with pigeons to examine the role of the signal in delayof-reinforcement procedures. In the first, a blackout accompanying a period of nonreinforcement increased key-peck response rates maintained by immediate reinforcement. The effects of dissociating the blackout from the delay interval were examined in the second experiment. In three conditions, blackouts and unsignaled delays were negatively correlated or occurred randomly with respect to one another. A signaled delay and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
61
2
7

Year Published

1988
1988
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 19 publications
12
61
2
7
Order By: Relevance
“…Using VI 60-s schedules, Schaal and Branch (1988) and Sizemore and Lattal (1977) found that short (1-to 9-s), unsignaled, nonresetting delays decreased key-pecking rates of pigeons. When such delays were signaled, rates similar to those that occur with immediate VI reinforcement were maintained (Schaal & Branch, 1988 (Ferster, 1953;Lattal, 1984;Schaal & Branch, 1990). In addition, Schaal and Branch (1990, Experiment 1) found that relatively long (27-s) delays that were briefly signaled could also maintain rates similar to those maintained by immediate reinforcement (cf.…”
mentioning
confidence: 97%
“…Using VI 60-s schedules, Schaal and Branch (1988) and Sizemore and Lattal (1977) found that short (1-to 9-s), unsignaled, nonresetting delays decreased key-pecking rates of pigeons. When such delays were signaled, rates similar to those that occur with immediate VI reinforcement were maintained (Schaal & Branch, 1988 (Ferster, 1953;Lattal, 1984;Schaal & Branch, 1990). In addition, Schaal and Branch (1990, Experiment 1) found that relatively long (27-s) delays that were briefly signaled could also maintain rates similar to those maintained by immediate reinforcement (cf.…”
mentioning
confidence: 97%
“…The procedures used by Lattal (1977, 1978), Ferster (1953), and Lattal (1984) seem to parallel delays to reinforcement as they occur in natural settings. At times (possibly rarely) delays to reinforcement are unsignaled (e.g., an elevator call button with no indicator light).…”
mentioning
confidence: 99%
“…These results may be contrasted with those of Ferster (1953), who found that rates of key pecking under a VI 60-s schedule could be maintained at baseline levels even with a 60-s delay of reinforcement, provided the delay was signaled (by a chamber blackout) and lengthened gradually. More recently, Lattal (1984), employing a modified VI schedule (which generated approximately 0.50 to 0.70 reinforcers per minute), found that when 20-s delays were signaled by a blackout rates of key pecking were maintained at values nearer immediate reinforcement baseline levels than when delays were unsignaled or when blackouts were not explicitly positively correlated with delays.…”
mentioning
confidence: 99%
“…In other studies, a stimulus change (such as handling by the experimenter or a brief tone or light) has been correlated with the start of the delay interval (e.g., Lett, 1975;Logan, 1952). Such stimuli may enhance response maintenance through conditioned reinforcing or other mediating effects, precluding interpretations of response acquisition strictly in terms of delayed reinforcement (e.g., Lattal, 1984;Schaal & Branch, 1988;Spence, 1947).…”
mentioning
confidence: 99%